Evolución de los derechos de los animales: análisis del caso de Estrellita (Tema Central) - Bravo Burbano, Ángela Cristina (2024)
Ecuador has been a pioneer in the recognition of rights of different subjects, than those covered by traditional positive law, but it cannot be ignored the jurisprudential precedents at the international level, as the case of the orangutan Sandra in Argentina, (2015) the case of the Atrato River in Colombia (2016). The case of the Ganges River in India (2017), among many others that have been supported by different arguments, moral and legal, so that questions, such as: Why should rivers be considered subjects of law, or Why should animals be considered subjects of law?, have solid arguments. Now the task is to define what rights assist each of the beings that make up nature. The Montecristi constitution enshrines some rights, and the Estrellita ruling expressly recognizes some rights to wild animals, such as the Right to physical integrity, to health, to feeding, to habitat, to express natural behaviors, however, etc. there are rights of beings that are part of nature, which today lack being a content Law and are define. This article, in addition to capturing a vision on the evolution of animal rights, aims to develop two rights that were recognized in the Estrellita sentence implicitly.